Plan de gestión y mejoramiento de recolección, transporte y disposición final de los residuos sólidos del cantón Piñas, año 2020 - Roblez Rogel, Alexis Daniel (My University, 2020)
This practical work makes an evaluation of the management of solid waste in the Canton of Piñas in the province of El Oro. By means of a survey carried out to the population of the canton and a visit to the sanitary landfill, the management of the waste that performs the municipality. Field work was also carried out in weighing the waste to different families, obtaining a per-capita value of 0.48 kg inhab day. The objective of this work is to find the problem that the Piñas Canton has regarding the management of solid waste in order to propose a management and improvement plan. Proposals for talks are made to make the population aware of making the proper separation of waste, making the proper closure of the landfill for reasons of being in its final stage, taking into account that there is no chamber for leachates. The municipality must accelerate the work of the new landfill of the Commonwealth to benefit from it and take advantage of the management that this will have, one of these is that they are going to compost to use the fertilizer, so it would be appropriate for the authorities to implement community gardens this being a benefit to society. They should also have a collection center for the recycling of inorganic waste, all this will minimize the amount of waste that will be disposed of in the aforementioned landfill.
El presente trabajo práctico hace una evaluación del manejo de los residuos sólidos del cantón Piñas de la provincia de El Oro. Por medio de una encuesta realizada a la población del cantón y visita al relleno sanitario, se hace constancia del manejo de los desechos que realiza el municipio. También se realizó labor de campo en el pesaje de los desechos a diferentes familias obteniendo un valor per-cápita de 0,48 kg hab día. El objetivo de este trabajo es encontrar la problemática que tiene el Cantón Piñas sobre el manejo de los residuos sólidos con el fin de proponer un plan de gestión y mejoramiento. Se realiza propuestas de charlas de concientizar a la población de hacer la adecuada separación de los desechos, hacer el adecuado cierre del relleno por motivos de estar en su etapa final teniendo en cuenta que no existe una cámara para los lixiviados. El municipio debe acelerar los trabajos del nuevo relleno de la Mancomunidad para beneficiarse del mismo y aprovechar el manejo que este va a tener, uno de estos es que van a realizar compost para utilizar el abono por lo que sería adecuado que las autoridades implementen huertos comunitarios siendo esto un beneficio a la sociedad. También deberían tener un centro de acopio para la realización de reciclaje de los desechos inorgánicos, todo esto minimizara la cantidad de desechos que serán evacuados en el relleno ya mencionado.
Keywords: RESIDUO SOLIDO; ENCUESTA; RELLENO; RECICLAJE